Analisis Hukum Penahanan Terhadap Tersangka di Masa Pandemi Covid-19 Pada Polsek Delitua - Zulkifli Harahap; Edi Warman; M. Citra Ramadhan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The purpose of this study was to analyze the legal rules governing the causal factors and actions taken by the Delitua Police in the event of a criminal act during the Covid-19 pandemic. This type of research is normative juridical research, namely research conducted by examining library materials (secondary data) or library law research. The results showed that the legal rules governing criminal acts that occurred during the Covid 19 period were regulated in government laws and regulations, namely the 1945 Constitution, the Criminal Procedure Code, Law No. 2 of 2002 concerning the police, Government Regulation No. 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) during the Covid period as well as other supporting regulations such as Presidential Regulations, Presidential Instruction, Governor Regulations, and Chief of Police Decrees. The factors that caused perpetrators to commit crimes during the Covid period were inter-factors, namely religion, economy and poverty as well as education, as well as external factors consisting of environmental factors, promiscuity and lack of government attention in providing social assistance. Efforts to tackle the occurrence of criminal acts during the Covid period, namely by making penal and non-penal efforts by providing counseling and socialization about maintaining health, washing hands, wearing masks for prison visitors, providing social assistance to each community equally.